Affect in ESP and Academic English: A Dynamic Systems Approach - Evangelia Xirofotou (Journal of English Language Teaching and Applied Linguistics, 2026)
Affect has long occupied an important place in second language acquisition (SLA), yet it has often been treated as a relatively stable learner variable that either facilitates or obstructs language input, participation and achievement. This conceptual paper argues that such a static treatment is insufficient for understanding academic English and English for Specific Purposes (ESP) learning in university English as a Foreign Language (EFL) contexts. Using a conceptual narrative review approach, this paper synthesizes foundational SLA theories, CDST scholarship, and contemporary research in ESP and academic English to reconceptualize affect as a dynamic, context-sensitive, and emergent system. It shows that emotions such as anxiety, confidence, enjoyment, boredom and self-efficacy fluctuate across tasks, assessment conditions, teacher feedback, peer interaction and disciplinary discourse demands. The argument is especially relevant to ESP and academic English classrooms, where learners are required not only to communicate in English but also to perform emerging academic and professional identities. The paper proposes pedagogical implications for task sequencing, classroom interaction, feedback and teacher responsiveness. It concludes by calling for longitudinal, classroom-based and process-oriented research that can capture affective change over time rather than relying only on one-time measures.